ACTUARIAL VERSUS SINKING FUND TYPE FORMULA FOR VALUATION. - Guthmann, H. G. (The Accounting Review, 1930)
This article compares actuarial formula with sinking fund type formula for valuation. The objections to all sinking fund type formula are generally over-ridden with too great ease. This fault involves a fundamental question of financial policy, which it would seem is sufficient to cause the rejection of all sinking fund type methods of valuation and the use of the so-called compound interest actuarial method for all commercial situations save those in which some contractual or statutory requirement actually calls for a bona fide sinking fund. Under the compound interest actuarial premises the capitalist receives at the end of each year simple interest upon the amount of capital he has outstanding at the beginning of each year. The distinguishing feature of all sinking fund valuation methods is that no capital of the original commitment may be returned to the investor during period of investment. A sinking fund is created, or assumed for the purpose of valuation, in which any capital return from receipts is placed.